Single-Channel Seismic Images from the Mediterranean Sea and Eastern North Atlantic Ocean acquired during the R/V Robert D. Conrad expedition RC0912 (1965) (IEDA: Marine-Geo Digital Library, 2004)
This data set was acquired with the LDEO Single-Channel Seismic system during R/V Robert D. Conrad expedition RC0912 conducted in 1965 (Chief Scientist: Dr. Maurice Ewing). These data files are of JPEG format and include Single-Channel Reflection Seismic images that have not been processed after acquisition.